Human umbilical cord-derived mesenchymal stem cells alleviate autoimmune hepatitis by inhibiting hepatic ferroptosis - Yaqin Li; Bing Liu; Guoxin Hu; Tao Zhou; Xuanqiu He; Ling Guo; Luoshi Zhang; Weizhao Tong; Yihua Chen; Youhua Xu; Guangdong Tong; Wei V. Zheng (PLoS ONE, 2025)
Background Autoimmune hepatitis (AIH) is a liver disease marked by immune-mediated hepatocyte damage. Current treatments have variable patient responses and considerable side effects, highlighting the need for alternative therapies. Human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) have shown therapeutic potential in liver diseases, but their mechanisms in AIH remain unclear. Methods A Concanavalin A (ConA)-induced AIH-like mouse model was used to assess the therapeutic effects of hUC-MSCs. Survival, liver function-related serum marker expression, histopathology, and apoptosis were evaluated. Metabolomic profiling and ferroptosis-related markers were analyzed to uncover potential mechanisms. Results In ConA-induced AIH-like mouse model challenged with a lethal dose of ConA, hUC-MSC treatment significantly ameliorated liver tissue damage and serum liver function parameters, alleviated hepatocyte apoptosis, and improved survival. Metabolomic and ontology analyses of mouse liver tissue samples revealed that hUC-MSCs treatment altered the levels of metabolites (Glu derivatives and peptides) functionally associated with ferroptosis-related pathways. hUC-MSCs partially reversed ConA-induced malondialdehyde (MDA), oxidized glutathione (GSSG), glutamate, and Fe 2+ , while restoring reduced glutathione (GSH). Expression of COX2 was downregulated, whereas key ferroptosis suppressors, SLC7A11, GPX4, and FTH1, were upregulated following hUC-MSC treatment. Conclusions Based on the above evidence, we propose that hUC-MSCs may ameliorate ConA-induced liver injury in mice, potentially through modulation of ferroptosis-related pathways, and we support further investigation of hUC-MSCs as potential treatments for AIH. We believe that further in-depth studies are still needed to elaborate on the detailed regulatory mechanisms of MSCs on the ferroptosis pathway during the treatment of AIH.